How Effective is Property Right to Deter Deforestation in Indonesia 2001-2005 - Rokhedi Priyo Santoso (Economic Journal of Emerging Markets, 2009)
The rate of deforestation in Indonesia is higher than the world average. The lack of propertyrights could potentially result in overexploitation on forest resources. This paper argues thatthe presence of assigned property rights (natural forest concession) would prevent furtherdeforestation in Indonesia. Using panel data estimation, the main result is that natural forestconcession is negatively significant in influencing deforestation in Indonesia. This effect isexplained by relatively high of the elasticity of deforestation rates with respect to area of assignednatural forest concession accounted for 0.33. This elasticity outweighs the positivesignificant effect of logs production in worsening deforestation in Indonesia.Keywords: deforestation, property right, natural forest concession, panel data